2014
DOI: 10.1038/nrcardio.2014.64
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic peptides in cardiometabolic regulation and disease

Abstract: In the 30 years since the identification of the natriuretic peptides, their involvement in regulating fluid and blood pressure has become firmly established. Data indicating a role for these hormones in lifestyle-related metabolic and cardiovascular disorders have also accumulated over the past decade. Dysregulation of the natriuretic peptide system has been associated with obesity, glucose intolerance, type 2 diabetes mellitus, and essential hypertension. Moreover, the natriuretic peptides have been implicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(115 citation statements)
references
References 147 publications
4
106
0
Order By: Relevance
“…Cardiac NPs are increasingly recognized as hormones with a wide spectrum of targets: In addition to traditional targets of vasculature and kidney, recently their effects on skeletal muscle mitochondrial biogenesis, angiogenesis, lipolysis, and adipose tissue remodeling (browning) have been reported (27)(28)(29)32). Although the present study focuses on one aspect of this signaling network, intramuscular cGMP signaling and mitochondrial biogenesis, it is possible that other cardiac NP signaling targets are similarly affected.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Cardiac NPs are increasingly recognized as hormones with a wide spectrum of targets: In addition to traditional targets of vasculature and kidney, recently their effects on skeletal muscle mitochondrial biogenesis, angiogenesis, lipolysis, and adipose tissue remodeling (browning) have been reported (27)(28)(29)32). Although the present study focuses on one aspect of this signaling network, intramuscular cGMP signaling and mitochondrial biogenesis, it is possible that other cardiac NP signaling targets are similarly affected.…”
Section: Discussionmentioning
confidence: 90%
“…NP/cGMP signaling is increasingly recognized as a key regulator of metabolic homeostasis, including effects on skeletal muscle mitochondrial biogenesis and oxidative phosphorylation potential (27)(28)(29). Maximal aerobic capacity (V · O 2max )…”
Section: Normal Musclin Signaling Promotes Mitochondrial Biogenesis Inmentioning
confidence: 99%
“…They are synthesized as pre-pro-hormones and undergo proteolytic cleavage of the propeptide by serine proteases to produce the mature natriuretic peptide [45] [46]. The effects of these peptides are widespread and include regulation of blood volume, blood pressure, ventricular hypertrophy, pulmonary hypertension, fat metabolism and long bone growth in response to a number of pathological conditions [47]. In this study, the natriuretic peptide transcripts identified from the Pseudonaja proteomes also exhibit the typical 17 membered ring (Figure 4).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Second, our risk score was developed in a Japanese urban population, and thus, although this score might be useful for Asian pathogenesis of overweight/obesity is related to increasing BP 21 and the sympathetic nervous system, 22 and it involves metabolic dysregulation. 23 Smoking is a modifiable risk factor for AF. 24, 25 A recent meta-analysis revealed that current smokers (relative risk=1.39; 95% CI, 1.11-1.75) and former smokers (1.16; 1.00-1.36) had an increased risk of AF compared with never-smokers.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%